THE FLEXURAL RIGIDITY OF FENNOSCANDIA : REFLECTION OF THE TECTONOTHERMAL AGE OF THE LITHOSPHERIC MANTLE - Poudjom Djomani Y.H.; Derek Fairhead J.; Griffin W.L. (My University, 1999)
Estimates of effective elastic thickness (Te), a measure of the strength of the plate, have shown that older and cool cratonic regions are characterised by a stronger lithosphere (higher Te values) than areas which have been tectonically reworked. We use geophysical data and information from xenoliths in volcanic rocks from Fennoscandia and show that the strength of the lithosphere reflects the tectonothermal age of the lithospheric mantle. Fennoscandia is made up of the Baltic shield (1.9–3.0 Ga) and the Caledonian Orogen of Norway and northern Sweden (400–500 Ma). The shield is characterised by an old, thick and cold lithosphere in contrast to the Caledonides where the lithosphere is hotter and thinner. Our geophysical analysis results show a regional variation in elastic plate thickness from 8 km to 70 km, or equivalently, a flexural rigidity between 0.4×1022 and 3×1024 Nm. These results suggest that the lithosphere is strongest in the relatively stable Archaean Province, weaker in the regions characterised by Proterozoic crustal formation, and lowest in the tectonically reworked and deformed Caledonian belt. Within the study area, there is a direct correlation between lithosphere strength, the age of the last major tectonothermal event registered in the crust and lithospheric mantle composition. These broad correlations reflect thinner and more fertile lithosphere, and higher geothermal gradients, beneath regions of progressively younger crust.
Keywords: Proterozoic; Archaean; Precambrian::Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Докембрий::Архей